Syntactic variation : the dialects of Italy - D'Alessandro, Roberta, 1973-; Ledgeway, Adam.; Roberts, Ian G. (Cambridge, U. K. : Cambridge University Press, 2010)
'The study of Romance languages can tell us a great deal about sentence structure and its variation in general. Focusing on the dialects of Italy - including the islands of Sardinia and Sicily - the authors explore three thematic areas: the nominal domain, the verbal domain and the left periphery of the clause. The book gives fresh attention to the dialects, arguing that they offer an unprecedented degree of variation (not found, for example, in Germanic languages). Analysing a host of new data, the authors show how the dialects can be used as a test-bed for investigating and challenging received ideas about language structure and change. Coherent and wide-ranging, this is a vital resource for those working in syntactic theory, historical linguistics, and Romance languages'--Provided by publisher.
'In particular, the books brings together a rich and varied collection of essays on a number of topics in Italian dialect syntax written by leading researchers in the field of Italian dialectology and, in many cases, also in the field of syntactic theory. The 17 essays, which fall into three thematic areas of the nominal domain, the verbal domain and the left periphery of the clause, present data from the dialects of northern, central and southern Italy, as well as the islands (Sardinia, Sicily), that directly bear on a range of diachronic and synchronic issues and problems'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Italian language -- Dialects -- Syntax; Italian language -- Syntax